(untitled) (Journal of Engineering, 2023)
Nanoparticles are defined as an organic or non-organic structure of matter in at least one of its dimensions less than 100 nm. Nanoparticles proved their effectiveness in different fields because of their unique physicochemical properties. Using nanoparticles in the power field contributes to cleaning and decreasing environmental pollution, which means it is an environmentally friendly material. It could be used in many different parts of batteries, including an anode, cathode, and electrolyte. This study reviews different types of nanoparticles used in Lithium-ion batteries by collecting the advanced techniques for applying nanotechnology in batteries. In addition, this review presents an idea about the advantages and disadvantages of using nanoparticles in batteries to harness energy without harming the environment. This review showed that applying nanotechnology and using nanoparticles in the production technique of batteries open the field for developing energy storage in Nano sized batteries. This, in turn, is important in the new era of technology in the industries of electronic devices and precision electrical appliances such as mobile phones, digital cameras, etc.